Analysis of results in patients after treatment using various segmental bone alloplasty techniques - Ya. O. Holovina; R. V. Malyk; O. Ye. Vyrva (Zaporožskij Medicinskij Žurnal)
Restoration of bone, adjacent joint and surrounding soft tissue integrity is an important factor in achieving full function of affected limbs in patients with bone tumors. Biological bone reconstruction has a number of advantages over other artificial implants.